(untitled) (Iraqi Journal of Medical Sciences, 2018)
Background: Legionella pneumophila (L. pneumophila) is gram-negative bacterium, which causes Legionnaires’ disease as well as Pontiac fever. Objective: To determine the frequency of Legionella pneumophila in pneumonic patients, to determine the clinical utility of diagnosing Legionella pneumonia by urinary antigen testing (LPUAT) in terms of sensitivity and specificity, to compares the results obtained from patients by urinary antigen test with q Real Time PCR (RT PCR) using serum samples and to determine the frequency of serogroup 1 and other serogroups of L. pneumophila. Methods: A total of 100 pneumonic patients (community acquired pneumonia) were enrolled in this study during a period between October 2016 to April 2017; 92 samples were collected from patients attended and admitted to Al-Imamein Al-Kadhimein Medical City and 8 samples from those in the (Center of Kidney Diseases and Transplantation) in the Medical City of Baghdad. All patients were under therapy with antibiotics. Serum and urine specimens were obtained from all patients; urine samples were processed for urinary antigen test (rapid test). Serum samples were collected and submitted to DNA extraction for detection of L. pneumophila mip gene by q RT PCR assay. Results: The percentage of L. pneumophila in two hospitals in Bagdad was 30%. Of these 26% was serogroup 1 detected by urinary antigen testing (UAT). In the other hand, 23% of samples were positive by q RT PCR based mip gene, of these 19 % were serogroup 1 and 4% were another serogroup. The sensitivity of UAT is high (P value < 0.001), which means statistically highly significance than q RT PCR. Conclusion: LPUAT is a rapid tool for early diagnosis of Legionella infection, which highlights the need of using this test in hospitals and health institutions and there is a high prevalence of L. pneumophila in Iraq that refer to the necessity of considering this microorganism point of view in future studies for detection and treatment in pneumonic patients. Keywords: L. pneumophila, mip gene, quantitative real time PCR, urinary antigen. Citation: Gauad SA, Abdulrahman TR, Muhamad AK, Jawad AA, Hassan JS. Clinical utility of urinary antigen test and molecular method for detection of Legionella pneumophila. Iraqi JMS. 2018; 16(2): 207-215. doi: 10.22578/IJMS.16.2.13